INTERMEDIATE CLEAVAGE PEPTIDASE55 Modifies Enzyme Amino Termini and Alters Protein Stability in Arabidopsis Mitochondria. Issue 2 (10th April 2015) - Huang, Shaobai; Nelson, Clark J.; Li, Lei; Taylor, Nicolas L.; Ströher, Elke; Petereit, Jakob; Millar, A. Harvey
Abstract : A mitochondrial protease alters the stability of proteins in Arabidopsis by removal of a single amino acid from their sequence. Abstract: Precursor proteins containing mitochondrial peptide signals are cleaved after import by a mitochondrial processing peptidase. In yeast ( Saccharomyces cerevisiae ) and human ( Homo sapiens ), INTERMEDIATE CLEAVAGE PEPTIDASE55 (ICP55) plays a role in stabilizing mitochondrial proteins by the removal of single amino acids from mitochondrial processing peptidase-processed proteins. We have investigated the role of a metallopeptidase (At1g09300) from Arabidopsis ( Arabidopsis thaliana ) that has sequence similarity to yeast ICP55. We identified this protein in mitochondria by mass spectrometry and have studied its function in a transfer DNA insertion line ( icp55 ). Monitoring of amino-terminal peptides showed that Arabidopsis ICP55 was responsible for the removal of single amino acids, and its action explained the −3 arginine processing motif of a number of mitochondrial proteins. ICP55 also removed single amino acids from mitochondrial proteins known to be cleaved at nonconserved arginine sites, a subset of mitochondrial proteins specific to plants. Faster mitochondrial protein degradation rates not only for ICP55 cleaved protein but also for some non-ICP55 cleaved proteins were observed in Arabidopsis mitochondrial samples isolated from icp55 than from the wild type, indicating that a complicated protease degradation network has been affected. The lower protein stability of isolated mitochondria and the lack of processing of target proteins in icp55 were complemented by transformation with the full-length ICP55. Analysis of in vitro degradation rates and protein turnover rates in vivo of specific proteins indicated that serine hydroxymethyltransferase was affected in icp55 . The maturation of serine hydroxymethyltransferase by ICP55 is unusual, as it involves breaking an amino-terminal diserine that is not known as an ICP55 substrate in other organisms and that is typically considered a sequence that stabilizes rather than destabilizes a protein.